2021
DOI: 10.2147/ijgm.s345050
|View full text |Cite
|
Sign up to set email alerts
|

Origin of Sepsis Associated with the Short-Term Mortality of Patients: A Retrospective Study Using the eICU Collaborative Research Database

Abstract: Objective The aim of this study was to compare the clinical characteristics and short-term mortality of patients with abdominal and pulmonary sepsis. Design Retrospective cohort study. Setting Adult intensive care units (ICUs) at tertiary hospitals. Participants Adult ICU patients from 2014 to 2015 in the eICU Collaborative Research Database. Interventions In univariate analysis, we comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…In recent years, a series of risk factors have been identified as predictors of death from septic shock, including old age, serum lactate level, red blood cell distribution width, blood urea nitrogen level, creatinine level, and SOFA score [25][26][27][28][29][30] . Despite the development of therapeutic agents and strategies for treating septic shock, the mortality rate remains consistently high among critically ill patients 4,[31][32][33][34] . Therefore, there is an urgent need to identify more effective indicators for evaluating outcomes of septic shock.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, a series of risk factors have been identified as predictors of death from septic shock, including old age, serum lactate level, red blood cell distribution width, blood urea nitrogen level, creatinine level, and SOFA score [25][26][27][28][29][30] . Despite the development of therapeutic agents and strategies for treating septic shock, the mortality rate remains consistently high among critically ill patients 4,[31][32][33][34] . Therefore, there is an urgent need to identify more effective indicators for evaluating outcomes of septic shock.…”
Section: Discussionmentioning
confidence: 99%
“…Two studies from China compared lung and abdominal sepsis; one showed lung infection was an independent risk factor for worse 1-year outcome and quality of life, while the other reported the complete opposite finding. 28 , 29 In our study, lung infection was shown to be associated with both increasing 30-day and 3-year mortality when compared with infection from a non-lung source.…”
Section: Discussionmentioning
confidence: 51%
“…While abdominal infection constitutes the second-most common cause of hospitalized sepsis, it has the greatest potential for morbidity and mortality (17,19). As observed by Volakli et al (19), critically ill patients with abdominal infections were more commonly admitted in septic shock and more likely to experience early coagulation and renal failure.…”
Section: Discussionmentioning
confidence: 99%
“…While the abdomen is the second most common source for sepsis behind the lung, it has the highest associated mortality (17,18). Patients with intra-abdominal infection are more likely to develop septic shock, coagulation failure, and renal failure compared with patients with respiratory infection (19).…”
Section: Introductionmentioning
confidence: 99%